Civil Society Organization Bidang Lingkungan: Studi Kasus Komunitas Jatinangor Hijau (Lembaga Pengembangan Kinerja Dosen, 2026)
This research analyzes the role of civil society organizations in the environmental field through a case study of Jatinangor Hijau Community. Using a descriptive qualitative approach, data were collected through in-depth interviews and document studies to examine the community's strategies and contributions in addressing waste problems in the Jatinangor Area. Findings indicate that the community serves as a multi-stakeholder collaboration facilitator through environmental education programs, public awareness campaigns, and policy advocacy. Theoretically, the community's existence represents the actualization of civil society organization within Alscher & Priller's (2010) framework with characteristics of organizational autonomy, voluntary participation, and public good orientation. This research also identifies the adaptive capacity of local civil society organizations in creating participatory spaces and strengthening deliberative democracy practices at the grassroots level. The research implications enrich the discourse on civil society organizations' contributions to environmental governance and local community resilience.